Effect of face-to-face awareness training on the anxiety of patients with COVID-19: A quasi-experimental study - Saeideh Azizi Mahkooyeh; Arezoo Rasti; Atefeh Asadpur Asl; Soheil Rahimi; Mohammadreza Kordbagheri (حیات, 2021)
Background & Aim: COVID-19 as an emerging disease has many psychological effects, including anxiety. The purpose of this study was to investigate the effect of face-to-face awareness training on anxiety of patients with COVID-19. Methods & Materials: In this study, 90 hospitalized patients in the hospitals affiliated to Tehran University of Medical Sciences in 2020 were selected using the convenience sampling method and randomly divided into two groups of intervention and control (45 people in each group). The DASS-21 anxiety and demographic information questionnaire were completed by both groups before the intervention. The face to face awareness sessions were provided during two 30-minute sessions at 24-hour intervals for the intervention group and the DASS-21 questionnaire was completed again by the patients one day after the second session. The control group received the routine information of the ward and completed the questionnaire again. The SPSS software version 21 was used for the data analysis by descriptive and inferential statistics. Results: The results showed that before the intervention, there was no statistically significant difference (P>0.05) in the mean anxiety scores between the intervention (12.71±9.20) and control (14.71±7.08) groups. But after the intervention, a significant difference was observed in the mean scores between the intervention (5.68±5.64) and control (12.75±6.19) groups (P˂0.05). Conclusion: This study revealed that face-to-face awareness training can reduce anxiety in patients with COVID-19 and can be used in medical centers.